ANALISIS LAYANAN KONSUMEN DI PDAM TIRTA DARMA KABUPATEN REJANG LEBONG - Pefriyadi, Pefriyadi (Creative Research Management Journal, 2022)
This study aims to determine the level of service to consumers at PDAM Tirta Darma, RejangLebong Regency. The research method used in this study is a qualitative method. Datacollection techniques in this study were carried out through observation, interviews anddocumentation. While the main sources of information in this study are consumers fromPDAM Tirta Darma, Rejang Lebong Regency. The results of this study are consumers whouse the services of products and services from PDAM Tirta Darma, Rejang Lebong Regency,returning 13,000 customers, service facilities are very adequate, good form of service, as wellas responsive, solutional and accommodating services. So that the services provided byPDAM Tirta Darma, Rejang Lebong Regency to consumers are very good. The weakness inthis study lies in the questioning activity, many of the answers given by the resource personsare not in accordance with the existing questions. The results of the research become asource of information for readers, consumers and employees at PDAM Tirta Darma, RejangLebong Regency, and can be a reference for other research. In this study, readers areexpected to know what services are available at PDAM Tirta Darma, Rejang LebongRegency, among others, oral services, written services and services in the form of actions